Effective academic leadership of learning and teaching in Malaysian higher education - Fahimirad, Mehrnaz; Idris, Khairuddin; Kotamjani, Sedigheh Shakib (Macrothink Institute, 2016)
his study provides an in-depth look at the practices of leadership in selected Malaysian Universities that have been identified as academic leadership. The findings of this study support the fundamental elements that have been previously identified by researchers and professional organizations, as academic leadership. Specifically, academic leaders focus on learning and teaching for students in relation to instructor development. This study employs a qualitative research approach. Thematic method was used to analyze the data. Data were collected through in-depth interview. Based on the findings of this study leadership works towards the future of the university through the development and involvement of instructors to facilitate teaching and learning at Malaysian universities. Based on the obtained results, Malaysian universities planned through sustained programs of educational development to use principles of learning and teaching effectively in designing learning environments for students. Secondly, academics need a supportive culture to put these principles into practice. To date creating learning culture depends not only on well-educated, well-meaning individual academics, but also on an academic community working together to create a student-centered attitude.